2003
DOI: 10.1002/ceat.200301844
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamics and Mass Transfer in Gas‐Liquid‐Solid Circulating Fluidized Beds

Abstract: Although extensive work has been performed on the hydrodynamics and gas-liquid mass transfer in conventional three-phase fluidized beds, relevant documented reports on gas-liquid-solid circulating fluidized beds (GLSCFBs) are scarce. In this work, the radial distribution of gas and solid holdups were investigated at two axial positions in a GLSCFB. The results show that gas bubbles and solid particles distribute uniformly in the axial direction but non-uniformly in the radial direction. The radial nonuniformit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(21 citation statements)
references
References 13 publications
(16 reference statements)
1
20
0
Order By: Relevance
“…The demonstration agrees with the experimental observations of Li (1998) and Wang et al (2003) and can be interpreted as follows. First, the gas-solid contact can be improved by the dynamic movement of clusters, which decreases the cluster shield effect and provides more effective gas-solid contacting area for the mass transfer.…”
Section: Multi-scale Mass Transfer Model 1647supporting
confidence: 86%
See 2 more Smart Citations
“…The demonstration agrees with the experimental observations of Li (1998) and Wang et al (2003) and can be interpreted as follows. First, the gas-solid contact can be improved by the dynamic movement of clusters, which decreases the cluster shield effect and provides more effective gas-solid contacting area for the mass transfer.…”
Section: Multi-scale Mass Transfer Model 1647supporting
confidence: 86%
“…In order to prevent the fluidizing-gas air from being saturated by the stimulated naphthalene, a kind of inert resin-styrene particles (density: 1298 kg=m 3 ) was mixed with the naphthalene spheres (density: 1162 kg=m 3 ). This also made the particle mixture easily fluidizable (Li, 1998). The tested naphthalene particles had two different sauter mean diameters, 0.50 and 0.30 mm, and their corresponding size distributions are shown Table I.…”
Section: Procedures Of Model Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…Considering the effects of operating variables on ε S , it was found that the value ε S increased with increasing U G , d P or G S but decreased with increasing U L or μ L in TPCFBs as shown in Figures 3 and 4 (Cho et al, 2001a;Liu et al, 2003;Vatanakull et al, 2003;Razzak et al, 2007Razzak et al, , 2009). Regarding the G S in TPCFBs, Kim et al (2015) suggested Eq.…”
Section: Three-phase Circulating Uidized Beds (Tpcfbs)mentioning
confidence: 93%
“…It has been noted that the axial and radial distributions of ε S are relatively uniform in TPCFBs as well as LSCFBs at fully developed flow conditions, as shown in Figure 2, comparing with those of conventional fluidized beds. This could be due to the rapid liquid velocity which is higher than the terminal velocity of fluidized solid particles (Cho et al, 2001a;Zheng et al, 2002;Liu et al, 2003;Vatanakull et al, 2003;Cao et al, 2009). Effects of operating variables on the values of ε S and ε G in TPCFBs and LSCFBs are summarized in Figures 3-5.…”
Section: Phase Holdup and Flow Behavior In The Risermentioning
confidence: 99%